Staphylococcus aureus nasal carriage is associated with serum 25-hydroxyvitamin D levels, gender and smoking status. The Tromsø Staph and Skin Study - Olsen, Karina; Falch, Birgit Margrethe; Danielsen, Kjersti; Johannessen, Mona; Sollid, Johanna U Ericson; Thune, Inger; Grimnes, Guri; Jorde, Rolf; Simonsen, Gunnar Skov; Furberg, Anne-Sofie (European Journal of Clinical Microbiology & Infectious Diseases, 2011)
Vitamin D induces the expression of antimicrobial peptides with activity against Staphylococcus aureus. Thus, we studied the association between serum 25-hydroxyvitamin D (25(OH)D) and S. aureus nasal colonization and carriage. Nasal swabs, blood samples and clinical data from 2,115 women and 1,674 men, aged 30–87 years, were collected in the Tromsø Staph and Skin Study 2007–08, as part of the population-based sixth Tromsø Study. Multivariate logistic regression analyses were stratified by recognized risk factors for S. aureus carriage: sex, age and smoking. In non-smoking men, we observed a 6.6% and 6.7% decrease in the probability of S. aureus colonization and carriage, respectively, by each 5 nmol/l increase in serum 25(OH)D concentration (P < 0.001 and P = 0.001), and serum 25(OH)D > 59 nmol/l and ≥75 nmol/l as thresholds for ~30% and ~50% reduction in S. aureus colonization and carriage. In non-smoking men aged 44–60 years, the odds ratio for S. aureus colonization was 0.44 (95% confidence interval, 0.28−0.69) in the top tertile of serum 25(OH)D versus the bottom tertile. In women and smokers there were no such associations. Our study supports that serum vitamin D is a determinant of S. aureus colonization and carriage.